Study on the distribution and habitat suitability of seagrass in the Northern Chinese Seas - Wang, Zhenhua; Ma, Qiaofeng; Liang, Shuxiu; Liu, Yu-an; Liu, Liming; Huang, Chao; Chen, Kexin; Hou, Wenhao (Frontiers in Marine Science, 2024)
Seagrass plays an important role in global coastal ecosystems but is among the least conserved marine ecosystems. The Northern Chinese Seas have abundant seagrasses. However, the limited information on their distribution and habitat suitability has hindered seagrass conservation and restoration in this area. The maximum entropy (MaxEnt) model was developed to study the distribution and habitat suitability of seagrasses. First, the model was developed using seagrass occurrence points and environmental variables data. The predictions were visualized using ArcGIS to create a map of potential seagrass distribution. Next, the Jackknife analysis tool and contribution rate were used to identify and quantify the dominant environmental variables. The predictions were analyzed to quantify the suitable range of the dominant environmental variables and determine the conditions for seagrass habitat suitability in the study area. Finally, the predictions were re-analyzed. By coupling the previous predictions and re-analysis results, the areas and suggestions for seagrass conservation and restoration were identified and recommended. The results indicated the predictions of the model were highly reliable, with a total potential seagrasses distribution area was 3,296.47 km2 in the study area. The distance from the shore, transparency, substrate type, SST, and nitrate concentration were identified as the dominant environmental variables. Seagrasses habitat suitability was high in study area when the distance from the shore was < 210 m, the SST was around 11 ~ 25°C, the substrate type was sandy with high mud content, the substrate particle size was around 35 ~ 330 µm, the transparency was around 0.7 ~ 1.5 m, and the nitrate concentration was< 6.4 mol·m-3. This was the first study in which seagrasses were investigated and predicted in the Northern Chinese Seas, and their potential distribution and suitable habitat conditions were assessed. Our work will not only provide fundamental information for coastal seagrass ecosystem management, but also serve as a method to support the conservation and restoration of seagrasses.